Risk aversion and engagement in the sharing economy - Jessica Santana; Paolo Parigi (Games, 2015)
The sharing economy is a new online community that has important implications for offline behavior. This study evaluates whether engagement in the sharing economy is associated with an actor's aversion to risk. Using a web-based survey and a field experiment, we apply an adaptation of Holt and Laury's (2002) risk lottery game to a representative sample of sharing economy participants. We find that frequency of activity in the sharing economy predicts risk aversion, but only in interaction with satisfaction. While greater satisfaction with sharing economy websites is associated with a decrease in risk aversion, greater frequency of usage is associated with greater risk aversion. This analysis shows the limitations of a static perspective on how risk attitudes relate to participation in the sharing economy.
Keywords: 330; risk; online; sharing economy